Penerapan Camels pada Bank Konvensional yang Listed di BEI - Imam Abrori; Abdurrahim Abdurrahim (Jurnal Ilmu Manajemen Advantage, 2019)
This study was conducted to examine the influence of Capital Adequacy Ratio (CAR), Biaya Operasional Terhadap Pendapatan Operasional (BOPO), Non-Performing Loan (NPL), Net Interest Margin (NPL) and loan to Deposit Ratio (LDR) to the Banking Profitability (ROA). Populations that are objects of this study are conventional banks listed on the Indonesia Stock Exchange. The method used in this research is to use multiple regression analysis to test the hypothesis that the t-test. Before using multiple regression analysis, performed classical assumption beforehand. From the results of the partial hypothesis test (t-test) in conventional banks showed that the CAR variable has no effect and no significant effect on bank profitability (ROA). Variable ROA and LDR significant negative effect on bank profitability (ROA), while variable NIM and NPL positive and significant impact on banking profitability (ROA). The ability of the independent variables affects the profitability of banks by 64% while the rest influence other variables not included in the research model.